Robert Aubrey Hinde CBE. 26 October 1923—23 December 2016. (5th December 2018) - Bateson, Patrick; Stevenson-Hinde, Joan; Clutton-Brock, Tim
Abstract : Robert Hinde led the study of animal behaviour for much of his long working life, drawing on his expertise in zoology and ethology to build bridges with psychology, psychiatry and the social sciences. He pioneered the application of a quantitative scientific approach to observations of behaviour, making important contributions to understanding underlying mechanisms, behavioural development and the dynamics of relationships between individuals. His influence on the field of animal behaviour was deep and pervasive, he was held in exceptionally high regard by others and his students and their students occupy many key positions in behavioural studies today. He went on to develop a science of personal relationships in humans, ranging from child development to the nature of aggression. Robert's dedication to research was combined with a commitment to promoting peace, including key roles in the Pugwash Conferences in Science and World Affairs. In retirement, he applied his ethological perspective to writing on the origins of religion and morality, the bases of war, and our culture of greed. Throughout his academic life he was a devoted member of St John's College, Cambridge—serving as teaching fellow, tutor and eventually Master.